Safety of Intraperitoneal Injection of Adipose Tissue‐Derived Autologous Mesenchymal Stem Cells in Cats. (29th October 2015) - Parys, M.; Nelson, N.; Koehl, K.; Miller, R.; Kaneene, J.B.; Kruger, J.M.; Yuzbasiyan‐Gurkan, V.
Abstract : Background: Chronic inflammatory diseases are common in cats and mesenchymal stem cells (MSC) are a promising therapeutic approach for management of these disorders. The purpose of this study was to evaluate the safety of intraperitoneal injection of MSC in cats. Hypothesis: Intrapertioneal injection of autologous MSC in cats is safe. Animals: Ten healthy adult purpose‐bred cats. Methods: Mesenchymal stem cells were isolated from subcutaneous adipose tissue collected during ovariohysterectomy and characterized for expression of CD90, CD105 and CD44 and trilineage differentiation. Three weeks postoperatively a complete blood count, serum chemistry profile, urinalysis, and abdominal ultrasound were performed. Five cats then received 1 × 10 6 of autologous MSC/kg of body weight intraperitoneally with ultrasound guidance; 5 additional cats were sham injected. Cats were monitored for 6 weeks with daily physical examinations and weekly clinicopathological evaluations. Abdominal ultrasonography was repeated at weeks 1 and 5 after injection. Results: Serious adverse effects were not observed in any MSC‐injected cat. Two animals developed transient lethargy and decreased activity. Jejunal lymph node size was increased in MSC‐injected cats compared to controls at weeks 1 (1.38 ± 0.25 versus 0.88 ± 0.25 cm 2 ; P = .036) and 5 (1.75 ± 0.82 versus 0.79 ± 0.12 cm 2 ; P = .047). A hyperechoic renal segmental cortical lesion was observed in 1 MSC‐injected cat. Conclusions and Clinical Relevance: Intraperitoneal MSC injection was well tolerated with only mild, self‐limiting adverse effects being observed in 2 cats. This route provides a safe means of administration for cell‐based treatment in cats.